2016
DOI: 10.1007/s11011-016-9823-0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of whole blood zinc and copper levels in children with autism spectrum disorder

Abstract: Zinc (Zn) and copper (Cu) are important trace elements for cognitive development and normal neurological functioning. Autism spectrum disorder (ASD) is a common neurological disorder, which has previously been associated with the levels of some trace elements in the blood. However, clinical data regarding the potential implication of Zn and Cu in patients with ASD are still insufficient. Therefore, the aim of the present study was to investigate the whole blood levels of Zn and Cu in a cohort of 28 children wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 26 publications
1
28
0
1
Order By: Relevance
“…Numerous people-based study suggested iron, zinc, iodine, folates and B vitamins might improve cognitive performance ( Nyaradi et al, 2015 ; Shah-Kulkarni et al, 2016 ; Portbury et al, 2017 ). In contrary, zinc and copper were believed to result in β-amyloid peptides aggregation which is one of the major pathological markers in the brain of AD patients ( ElAli et al, 2013 ; Crăciun et al, 2016 ). The reason of this inconsistent might be inappropriate analysis methods, different selection of sample and matching controls ( Modgil et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous people-based study suggested iron, zinc, iodine, folates and B vitamins might improve cognitive performance ( Nyaradi et al, 2015 ; Shah-Kulkarni et al, 2016 ; Portbury et al, 2017 ). In contrary, zinc and copper were believed to result in β-amyloid peptides aggregation which is one of the major pathological markers in the brain of AD patients ( ElAli et al, 2013 ; Crăciun et al, 2016 ). The reason of this inconsistent might be inappropriate analysis methods, different selection of sample and matching controls ( Modgil et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study suggests that increased levels of BPb in some children with ASD may trigger the production of serum anti-ribosomal P antibodies (Mostafa et al 2016b). It has been reported that ASD children often have a lower zinc (Zn)-to-copper (Cu) ratio in blood compared to healthy controls (Faber et al 2009, Li et al 2014, Crăciun et al 2016) and children with other neurological disorders (Macedoni-Lukšič et al 2015). It has been suggested that metallothionein (MT) dysfunction may occur as a cause of Hg accumulation in children with ASD, and the same dysfunction may also lead to Zn deficiency (Bjørklund 2013).…”
Section: Autoantibodiesmentioning
confidence: 99%
“…There is no detailed report on the action mechanisms related to psychological disorders and PSD95-3MT; therefore functional analysis in future studies might also be beneficial. In addition, there are some reports on psychological stress-induced zinc accumulation and MT upregulation in the liver, 93) and MT gene expression mediated by zinc was upregulated in children with autism spectrum disorder. 94) Furthermore, our laboratory reported that reduction of MT-3 might be induced by abnormal behaviors such as psychiatric disorders using MT-3 KO mice.…”
Section: Psychiatric Disordersmentioning
confidence: 99%